The bone hacker [compact disc, unabridged] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2023)
Young men-tourists-have been disappearing on the islands of Turks and Caicos for years. Seven years ago, the first victim was found in a strange location with both hands cut off; the other visitors vanished without a trace. But, recently, tantalizing leads have emerged and only Tempe can unravel them. Maddeningly, the victims seem to have nothing in common-other than the strange locations where their bodies are eventually found, and the fact that the young men all seem to be the least likely to be involved in foul play. Do these attacks have something to do with the islands' seething culture of gang violence? Tempe isn't so sure. And then she turns up disturbing clues that what's at stake may actually have global significance. It isn't long before the sound of a ticking clock grows menacingly loud, and then Temper herself becomes a target.